Business vertical integration in Ukraine: motivation, advantages and disadvantages - Chukhray, N. (Національний університет "Львівська політехніка", 2013)
The paper deals with the problems of increasing the competitiveness of Ukrainian enterprises and integration process in Ukraine. Correlation between a level of business vertical integration and development of a country is wellproven. Basic problems of the integration strategy of Ukrainian enterprises are identified. The author gives us the examples of successful development of the largest private vertically integrated energy company in Ukraine. One of the main directions of developing of the Ukrainian economy is to cooperate with the strategic partners as an important priority in the formation of vertical integrated structures of national importance.
Keywords: vertical integration; transition economy; the post-Soviet space; the defence-industrial complex (DIC); strategic partners; vertical integrated structures